In vitro antioxidant activity and enzyme inhibition properties of wheat whole grain, bran and flour defatted with hexane and supercritical fluid extraction. (July 2021) - Sahu, Ranabir; Kundu, Pritha; Sethi, Avinash
Abstract: Wheat, the most common cereal from the genus Triticum, owing to its immense food value ranks as the second most important crop worldwide. A diverse range of human health benefits is obtained from phenolics of whole wheat products. Here, two methods, namely, hexane and supercritical carbon dioxide fluid extraction (SC–CO2 ), have been deployed for the purpose of successful extraction of phenolic acids by defatting wheat whole grain, bran, and flour. SC-CO2 yielded 5.2–9.6% higher oil than hexane extraction. Total phenolic content (TPC) and individual phenolic acids content of esterified SC-CO2 defatted wheat whole grain (SWG) samples were 0.85–2.6-fold higher than its hexane counterpart. Ferulic acid and p- coumaric acid were more abounded phenolic acids in the wheat grain. A higher antioxidant capacity in DPPH, ABTS and phosphomolybdenum assay was observed in esterified SWG that corroborated with higher reducing activity by FRAP, CUPRAC assays, and metal chelating activity. An effective inhibitory activity of esterified SWG was observed against a-amylase, tyrosinase, lipase and acetylcholinesterase. Finally, positive correlation was found between TPC and its corresponding antioxidant and enzyme inhibitory activities. In summary, phenolics rich fraction, elevated antioxidant and enzyme inhibitory activities were aided in wheat grain defatted samples enriched with SC-CO2 . Highlights: Defatting of wheat whole grain, bran and flour with SC-CO2 yield higher. Identification and quantification of phenolic acids in wheat samples. Higher total and individual phenolic contents in samples defatted with SC-CO2 . Higher antioxidant activity and enzyme inhibition in samples defatted with SC-CO2 .